MicroRNA-199a-3p regulates proliferation and milk fat synthesis of ovine mammary epithelial cells by targeting VLDLR - Wang, Jiqing; Hao, Zhiyun; Hu, Liyan; Qiao, Lirong; Luo, Yuzhu; Hu, Jiang; Liu, Xiu; Li, Shaobin; Zhao, Fangfang; Shen, Jiyuan; Li, Mingna; Zhao, Zhidong (Frontiers in Veterinary Science, 2022)
In our previous study, microRNA (miR)-199a-3p was found to be the most upregulated miRNA in mammary gland tissue during the non-lactation period compared with the peak-lactation period. However, there have been no reports describing the function of miR-199a-3p in ovine mammary epithelial cells (OMECs) and the biological mechanisms by which the miRNA affects cell proliferation and milk fat synthesis in sheep. In this study, the effect of miR-199a-3p on viability, proliferation, and milk fat synthesis of OMECs was investigated, and the target relationship of the miRNA with very low-density lipoprotein receptor (VLDLR) was also verified. Transfection with a miR-199a-3p mimic increased the viability of OMECs and the number of Edu-labeled positive OMECs. In contrast, a miR-199-3p inhibitor had the opposite effect with the miR-199a-3p mimic. The expression levels of three marker genes were also regulated by both the miR-199a-3p mimic and miR-199-3p inhibitor in OMECs. Together, these results suggest that miR-199a-3p promotes the viability and proliferation of OMECs. A dual luciferase assay confirmed that miR-199a-3p can target VLDLR by binding to the 3′-untranslated regions (3'UTR) of the gene. Further studies found a negative correlation in the expression of miR-199a-3p with VLDLR. The miR-199a-3p mimic decreased the content of triglycerides, as well as the expression levels of six milk fat synthesis marker genes in OMECs, namely, lipoprotein lipase gene (LPL), acetyl-CoA carboxylase alpha gene (ACACA), fatty acid binding protein 3 gene (FABP3), CD36, stearoyl-CoA desaturase gene (SCD), and fatty acid synthase gene (FASN). The inhibition of miR-199a-3p increased the level of triglycerides and the expression of LPL, ACACA, FABP3, SCD, and FASN in OMECs. These findings suggest that miR-199a-3p inhibited milk fat synthesis of OMECs. This is the first study to reveal the molecular mechanisms by which miR-199a-3p regulates the proliferation and milk fat synthesis of OMECs in sheep.